Romaerne på fælleden: Om at krydse globale fortællinger - Frello, Birgitta (Academic Quarter | Akademisk kvarter, 2017)
Birgitta Frello's article The Roma Squatters on Amager Common deals with two narratives used to understand the situation of Roma people. On the one hand they cannot live up to the deep ingrained understanding that tells us that it is natural for all people to live and die in the country they were born in, the national narrative. On the other they cannot fit into liberalism's (and we could add postmodernism's) story about the positive possibilities inherent in the freedom to move through national borders, enjoying cultural hybridity, multiple identities, etc. Those are reserved for transnationalism from the top, but the Roma are placed among those who practice transnationalism from below: poor immigrants, refugees and others. Birgitta Frello uses the expulsion of some Roma people from Denmark in 2010 as a case study to shed light on the two narratives, their limitations and consequences.